EFFECTS OF PLYOMETRIC TRAINING ON THE SELECTED PHYSICAL FITNESS VARIABLES AMONG MALE U-13 ANALEMO VOLLEYBALL PROJECT PLAYERS, THE CASE OF ANA LEMOWEREDA, HADIYA ZONE, ETHIOPIA - Hundito, Dr. Biruk; Shigute, Behailu (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
The aim of this study was to investigate the effects of twelve weeks of plyometric training on selected physical fitness among u-13 male Analemo volleyball project players. This study was also creates the awareness for volleyball coaches to incorporate plyometric training when they design training program to develop volleyball player’s physical fitness. The study was designed census experimental and used 25 total size of project players, The participants of this study were classified into two groups by purposive sampling system; the experimental group (n=15) who performed plyometric training three days per week for 3 month and 60 mint per session and the control group (n=10) have undergone normal training programs. And both the control and experimental group had taken pretests and posttests. So, all subjects participated in 4 selected physical fitness performance tests: 35meter sprinting test, vertical jump test, V sit and reach test and Pro-agility test the data collected from the study subject were analyzed using SPSS version 21 software by paired sample test and independent sample test of significant at 0.05 level of confidence The polymetric training exercises was conducted Cone Jump, Multiple hops with a Sprint, jumps from different position and direction with cone, frog jump, lateral speed drill, Tuck jumps, sit and reach the foot and Squat jumps. The selected subjects were measured of their physical fitness components, speed, power, agility and flexibility. Descriptive statistics was calculation for statistical treatment. Plyometric training shows more improvement than from pre training session to post training session. The study of plyometric training exercises significantly to increase speed, power, flexibility and agility. The study has significantly improved speed, power, flexibility and agility.